Delay in the Service Confirmation of Selected Groups of Workers in the Government Health Service of Sri Lanka (International Journal of Scientific Research and Management (IJSRM), 2022)
Objective To describe the delay in service confirmation and to implement an intervention to improve timely confirmation for selected categories of employees, Regional Directorate of Health Services (RDHS), Hambantota, Sri Lanka. Methods Nursing Officers (NOs) and Health Service Assistants (HAS) were identified as the most affected by the delay. The documents needed for promotion and delays experienced already permanent employees (Group A) and post-probationers awaiting promotion (Group B) were described. An interventions was developed to enhance submitting documents and evaluation were done in phase 2 and 3 respectively. Results NOs and HSA in group A experienced mean delays of 83.1 weeks (SD 27.3) and 136.1 weeks (SD 75.6) with significant difference. Trend was similar in group B. Initiation of activities needed for promotion by RDHS has taken 170.2 (SD 8.7) weeks for NOO and 173.9 (SD 37.4) weeks for HSA in group B. HSA were less compliant in submitting documents. Heads of Institutions (HOI) showed delays in submitting annual reports. The intervention resulted in receiving all documents to be submitted by employees, and significant increase in receiving annual reports of HoI. It increased from 52.0 % to 74.0%. Recommendation of personal files of HSA for the promotion by Regional Director Hambantota (RDH) was increased (p <0.01, from 04% to 40%). Usage of the checklist to update personal files improved significantly from 0.9% to 71.2% (p<0.01). Conclusion The delays in promotion has affected all selected employees in RDHS, Hambantota. It has to be improved by regular supervision of processing of reqiured documents, and by early initiation of the process of promotion.